Screening of Inbred Lines and Hybrids/composites Against Common Rust of Maize under Field Conditions - Dey, Utpal; Harlapur, S. I.; Dhutraj, D. N.; Das, Anup (International Journal of Bio-resource and Stress Management, 2017)
The biotrophic fungus Puccinia sorghi Schw. is one of the most devastating pathogen causing significant yield losses in maize production and productivity. Although, chemical pesticide measures are effective in reducing yield losses, yet their use is restricted due to the high cost involvement and residual toxicity affecting the ecological balance. Thus, for minimizing the losses due to the disease, it is necessary to introgress an adequate level of genetic resistance against the disease having economic importance that will reduce the use of chemical pesticides. A field experiment has been conducted in the farm of Main Agricultural Research Station, College of Agriculture, University of Agricultural Sciences, Dharwad, Karnataka, India, on the screening of different inbred lines and hybrids/composites against common rust of maize incited by Puccinia sorghi Schw. The experiment was laid down in a randomized block design (RBD) with three replications. Significant differences in resistance to common rust of maize were found among the maize inbreds and hybrids tested. Among the 43 inbred lines 2 inbred lines viz., Indimyt 345 and MI-12 registered highly resistant reaction. Of the 43 hybrids/composites evaluated 14 lines, viz., NK-6240, NK-61, NK-7305, CP-808, GK-3090, 30R77, CP-818, C-1945, JKMH-502, PAC-740, NK-121, Pro-311 and DK-984 registered resistant reaction against P. sorghi. The study reveals that the nature of resistance to P. sorghi is inheritable as the hybrids derived from resistant inbreds were more resistant than those hybrids derived from the susceptible parents. The study concludes that screening parental inbred lines for resistance to P. sorghi is an important step in developing maize hybrids with improved resistance to P. sorghi.